Identifying Early Markers of "Late Onset" Attention Deficit and Hyperactivity/Impulsivity Symptoms. Issue 13 (November 2020) - Murray, Aja Louise; Eisner, Manuel; Obsuth, Ingrid; Ribeaud, Denis
Objective: In recent years, there has been an increased focus on "late onset" ADHD, referring to the onset of symptoms beyond childhood, into adolescence and adulthood. We aimed to identify childhood predictors of ADHD symptom increases over development.Method: We used growth mixture modeling to evaluate predictors of a "late onset" symptom trajectories in a longitudinal cohort study of youth measured at eight points from ages 7 to 15.Results: Individuals with high levels of sensation seeking at age 7 were more likely to show a trajectory of ADHD symptoms characterized by increasing levels from age 7 than persistently low symptom levels.Conclusion: The late versus early onset distinction may align with the distinction between deficits in "bottom-up" versus "top-down" processes previously discussed in relation to ADHD. Results also raise the possibility that later onset symptoms could be predicted based on characteristics in childhood.